PENINGKATAN PENGETAHUAN IBU HAMIL MELALUI EDUKASI PENCEGAHAN ANEMIA - Arnianti; Dewi Hastuty; Yuniar Dwi Yanti; Adeliana; Yenni (Poltekkes Kemenkes Bengkulu, 2026)
Background: Anemia is still a serious health problem in pregnant women in Indonesia, with a prevalence reaching 48.9%. This condition not only increases the risk of maternal and child mortality, but also has an impact on the quality of human resources as a whole. Therefore, handling anemia in pregnancy requires quality health interventions. Objective: This community service aims to improve the knowledge of pregnant women about preventing anemia. Method: This activity is carried out by providing education through leaflets, lectures, discussions, and question and answer sessions. The increase in knowledge is measured by comparing the results of the pretest and post-test descriptively. Results: Before education (pre test), only 33% of pregnant women had good knowledge. After education (post test), the percentage of pregnant women with good knowledge increased sharply to 73%. This figure shows a significant increase in knowledge. Conclusion: Health education about preventing anemia is effective in improving the knowledge of pregnant women.